Hearing Animals’ Stories: Interspecies Bond in Sanjeev Upreti’s Hansa - Upadhyay, Toya Nath (Bon Voyage, 2024)
This paper analyzes Sanjeev Upreti’s Hansa (Duck), published in 2076 BS (2019 AD) from the perspective of Literary Animal Studies with a major objective of unveiling the author’s awareness of the exigency of an equitable and sustainable animal-human bond in the contemporary Anthropocene. The novel unfolds twin narratives in which one is a human protagonist and another a duck. In both narratives, stories of animals are foregrounded. Animal characters narrate their own stories that consist of their grievances of cruelties and indifference they face at the hand of humans. The human protagonist hears and understand these stories. It raises a question: why does he hear their stories? After analyzing the textual evidence through the theoretical perspective of Literary Animal Studies by focusing on Susan McHugh’s concept of animal narrative agency, the paper finds the answer that the human protagonist hears the animals’ stories because they underscore narrative agency. Unlike conventional roles of animals as metaphors and symbols for the making of human identity, these animals play an active role in resisting human exploitation against them. Finally, the paper claims that by offering narrative agency to animal characters, the author highlights the need of building an entangled interspecies bond among human and nonhuman animals. With this, the study expects to be useful for those readers and researchers interested in the field of Literary Animal Studies.